Promoting exports industry and agriculture: the work of the Export and Industrial Development Division (Commonwealth Secretariat LondonGB)
Describes the work of the new Export and Industrial Development Division which now incorporates the Industrial Development Unit (IDU), the Export Market Development Division (EMD), and the Food Production and Rural Development Division (FPRD) of the commonwealth Secretatiat
DC